O sujeito metafísico e o declínio do indivíduo na sociedade administrada: um estudo das implicações do pensamento de Adorno no campo da educação - Silva, Raquel dos Santos Candido da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In the horizon of investigation about the nature of the self, studies guided by the metaphysical perspective historically played a determining role with regard to the conceptualization of the subject. With Descartes and Leibniz, the autonomy of the self as an independent category of concrete subjects postulated in man a being endowed with a set of peculiar characteristics, related to the founding principles of his entity and substance. Bearing in mind the historical process of constitution of the individual, Theodor W. Adorno delineates the subject as a sociological category inseparable from social life, since its ascension is mediated by social and objective relations. However, given the current stage of development of capitalism, formative processes of individual decay are inaugurated in which the bases that once allowed its consolidation are diluted, which corresponds to an integrated world. Current ways of managing life will be analyzed, with a view to introducing integration processes that work by submitting individual forces to what was rationally dictated as a whole. We will see how this attack on the conscience and self-determination of individuals develops numerous regressive processes, which make the formative process extremely retrograde.

No horizonte de investigação acerca da natureza do eu, os estudos orientados pela perspectiva metafísica desempenharam historicamente um papel determinante no que se refere à conceituação do sujeito. Com Descartes e Leibniz, a autonomia do eu como categoria independente dos sujeitos concretos postulou no homem um ser dotado do conjunto de características peculiares, relacionados aos princípios fundantes de sua entidade e substância. Tendo em vista o processo histórico de constituição do indivíduo, Theodor W. Adorno delineia o sujeito como categoria sociológica inseparável da vida social, pois a sua ascensão é mediada por relações sociais e objetivas. No entanto, diante da atual etapa do desenvolvimento do capitalismo, são inaugurados processos formativos de decadência do indivíduo nas quais são diluídas as bases que um dia permitiram a sua consolidação, o que corresponde a um mundo integrado. As atuais formas de administração da vida serão analisadas, tendo em vista a introdução de processos de integração que atuam submetendo forças individuais àquilo que foi ditado racionalmente ao conjunto. Veremos como esse ataque à consciência e à autodeterminação dos indivíduos desenvolvem inúmeros processos regressivos, que tornam o processo formativo extremamente retrógrado.
The metaphysical subject and the decline of the individual in society managed: a study of the implications of Adorno thought in the field of education
Keywords: Critical theory; Metaphysical subject; Individual; Teoria crítica; Theodor W. Adorno; Indivíduo; Sujeito metafísico